Transport modeling for a complete beginner - Hollander, Yaron, ....- (Ctthink!, 2016)
Finally! A book about transport modelling which doesn't require any previous knowledge. "Transport modelling for a complete beginner" explains the basics of transport modelling in a simple language, with lots of silly drawings, and without using any mathematics. Click here to watch a 3-minute introductory video (or search for the book name on YouTube if the link doesn't show). This book is aimed at transport planners, town planners, students in transport-related courses, policy advisors, economists, project managers, property developers, investors, politicians, journalists, and anyone else who wants to understand the process of making decisions on transport infrastructure. It is suitable for readers in any country.
Keywords: Economie; Stadsontwikkeling; Transport Modeling; Verkeer